Pentingnya Pendidikan Konservasi Untuk Menjaga Lingkungan Hidup (Studi Kasus di Desa Cidahu, Kabupaten Kuningan) - Rifqie Mardiansyah Purmadi; Dewa Made Juli Santika; Arum Sekar Wulandari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Education is an important role in the enhancement and development of human resources of a nation. Conservation education is an education that expects a change in behaviour, attitudes and thinking, especially related to the management of natural resources and their ecosystem. The other potential of Cidahu village is the great attention to the development of the village both from citizens and village officials. Conservation education is one of the programs conducted in Cidahu village. This activity raised the theme of